Kandungan Mineral Ã¢â‚¬Å“NikeÃ¢â‚¬Â Ikan Payangkah (Ophiocara aporos ) dari Danau Tondano di Sulawesi Utara - Sofia Krisen; Jeanne Tuerah (Jurnal Kimia Fullerene, 2022)
Research has been conducted on the Mineral Content of Ã¢â‚¬Å“nikeÃ¢â‚¬Â Payangkah fish (O. aporos ) from Lake Tondano in North Sulawesi. The research objective was to determine the levels of Calcium, Magnesium, Manganese and Phosphorus. "nike" Payangkah fish (O. aporos) is taken directly from Lake Tondano fish farmers in Minahasa Regency, North Sulawesi. Sample preparation techniques include receiving, washing, selecting other than Ã¢â‚¬Å“nikeÃ¢â‚¬Â Payang fish and associated materials (excrement). All parts of the fish body are used as samples. Determination of Ca, Mn and Mg using (AAS) while P using (UV-VIS). The results show that the average P content (259.6 mg/100g); Ca (380.3 mg/100g); Mn (0.275 mg/100g) and Mg (21.49 mg/100g). When compared with the average mineral content for fish released by (FAO), these results indicate that "nike" Payangka fish (O. aporos) has good mineral content and can be used to increase mineral intake and protect against mineral deficiency diseases